Aproximación al análisis fitosociológico de la flora algal del subestrato de Cystoseira mediterranea Sauv., en el litoral valenciano (España, Mediterráneo) - Gómez Garreta, Amelia; Boisset, F. (Botanica Complutensis, 1989)
A phytosociological studv of the flora that grows under the canopy of (ysíoseira mediterranea Sauv. in the Levantine coast of Spain (Mediterranean) is made. The results are in agreement with other ones from other sites of Western Me diterranean basin. The infralittoral photophilous species are the more conspicuous group.